Pengembangan Sistem Informasi Penunjang Pelayanan Hotel (Studi Kasus: Hotel XYZ) - Umar, Rusydi; Nugrahantoro, Achmad; Periyanto, Ari; Nugroho, Aji; Kharismajati, Gema; Susanto, Dwi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The hotel is a building that provides lodging services, restaurants, and other services that provide commercial for visitors. The use of hotel services that are still manual will be handled on the effectiveness of excellent service in hotel management. Computer technology support can be a solution in optimizing administrative activities, improving information, and making decisions. Hotel XYZ as one that still uses a manual transaction system. Then it is necessary to integrate data for each transaction using an interconnected database. Steps in the development of information systems need to be considered in improving the services of each hotel. The technique by collecting data to produce literature studies is an appropriate step to analyze the old system while developing the expected system. The results will be made on the design of the system for the database so that they are interconnected and the interface is easily understood by the user so that it facilitates the process of system implementation. After doing research, the black box test with a value of 100% with the results as expected is done. Comparison of the old system can be made by Microsoft Excel with interconnected databases presenting reports in printed form. It can meet the level of user satisfaction with a value of 95.3% of the results of the questionnaire from the five respondents involved.